Profile of HOTS ability (High Order Thinking Skill) level analysis of biological materials for SMA/MA students in-Banten Province - Afra Bilqis; Mila Ermila Hendriyani; Mahrawi Mahrawi; Dwi Ratnasari; Ika Rifqiawati (Journal on Biology and Instruction, 2021)
Banten is one of the provinces in Indonesia with the quality of education that has not been said to be good. One of the causes of the low quality of education is the low thinking ability of students. This research aimed to determine the HOTS (High Order Thinking Skill) ability analytical skill of biology material for SMA/MA students in Banten Province by used description question. The research method used is descriptive qualitative. The sampling technique used in this study was random sampling. The sample used was 320 students in Banten Province. The instrument used was a description of the analytical skills, interview sheets and questionnaire sheets. The research was conducted from March to November 2020. Based on the results of the research, the average analytical ability of students in Banten Province was in the less category with a score of 22,19.